Dread and hope Christian eschatology and pop culture - Wise, Joshua (Lanham Lexington Books/Fortress Academic, 2022)
"Dread and Hope brings early Christian hopes concerning the consummation of the cosmos and modern apocalyptic pop-culture into dialog. Drawing from a wide range of research and media, Joshua Wise examines how figures like Antiochus IV, Damien from The Omen, the Emperor Nero, and Winston Smith from Orwell's 1984 inform each other"--
Includes bibliographical references and index
Keywords: Eschatology -- Biblical teaching; Eschatology; Popular Culture -- Religious aspects -- Christianity